1989
DOI: 10.1136/bmj.299.6696.423
|View full text |Cite
|
Sign up to set email alerts
|

Passive smoking and cardiorespiratory health in a general population in the west of Scotland.

Abstract: Objective-To assess the risk of cardiorespiratory symptoms and mortality in non-smokers who were passively exposed to environmental smoke.Design-Prospective study of cohort from general population first screened between 1972 and 1976 and followed up for an average of 11-5 years, with linkage of data from participants in the same household.Setting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
1
2

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(88 citation statements)
references
References 15 publications
2
83
1
2
Order By: Relevance
“…Among adults, the impact of ETS on pulmonary function has been less clear. In several studies, self-reported ETS exposure was associated with decreased FEV 1 , FVC, or FEV 1 /FVC ratio (27)(28)(29)(30)(31)(32)(33). Supporting these deleterious effects of ETS, we found an increase in pulmonary function among 53 bartenders after reduction in workplace ETS exposure during an 8-week period (34).…”
Section: Discussionsupporting
confidence: 62%
“…Among adults, the impact of ETS on pulmonary function has been less clear. In several studies, self-reported ETS exposure was associated with decreased FEV 1 , FVC, or FEV 1 /FVC ratio (27)(28)(29)(30)(31)(32)(33). Supporting these deleterious effects of ETS, we found an increase in pulmonary function among 53 bartenders after reduction in workplace ETS exposure during an 8-week period (34).…”
Section: Discussionsupporting
confidence: 62%
“…Concern about confounding is further reduced by the results of five other studies that show both age-adjusted and multivariate RR estimates for CHD associated with spousal smoking (3,12,13,18,22). In three of these studies the RR estimate increased after multivariate adjustment (12,13,22); in the remaining two (3,18), the RR estimate decreased slightly, as it did in the Nurses' Health Study (4 (42).…”
Section: Confoundingmentioning
confidence: 89%
“…In three of these studies the RR estimate increased after multivariate adjustment (12,13,22); in the remaining two (3,18), the RR estimate decreased slightly, as it did in the Nurses' Health Study (4 (42). The age-adjusted prevalence of self-reported hypertension, diabetes, and increased cholesterol was slightly (1-3%) higher among ETS-exposed nurses than among the unexposed.…”
Section: Confoundingmentioning
confidence: 90%
See 2 more Smart Citations